2011
DOI: 10.1016/j.jpeds.2010.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Age at Onset of Puberty Predicts Bone Mass in Young Adulthood

Abstract: Objective To determine whether the commencement and length of puberty influences dual x-ray absorptiometry (DXA) values of bone mineral content (BMC) and bone mineral density (BMD) in the axial and appendicular skeleton at skeletal maturity. Study design From the Bone Mineral Density in Childhood Study, we identified children who began puberty and completed sexual and skeletal development and examined whether the timing and length of puberty influence DXA values of BMC and BMD at skeletal maturity. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(70 citation statements)
references
References 26 publications
7
63
0
Order By: Relevance
“…Most studies report that late commencement of puberty is associated with lower BMD in both sexes [26,28,39]. For girls with intermediate and late sexual maturation, we found a negative association with BMD levels at the femoral neck as described by Heaney 2000; who reported that late menarche is a skeletal disadvantage, and that there is an association between age at menarche and fracture risk.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Most studies report that late commencement of puberty is associated with lower BMD in both sexes [26,28,39]. For girls with intermediate and late sexual maturation, we found a negative association with BMD levels at the femoral neck as described by Heaney 2000; who reported that late menarche is a skeletal disadvantage, and that there is an association between age at menarche and fracture risk.…”
Section: Discussionsupporting
confidence: 78%
“…Most studies report that late menarche is associated with lower BMD [26]. In the Lunar reference, the puberty data, if collected, were collected in different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Pubertal timing affects BMD accrual during adolescence, (12)(13)(14)22) and has been reported to be associated with BMD in adulthood and old age in women in several, but not all, studies. (1,(5)(6)(7)(23)(24)(25)(26) This relationship has been mainly studied in women, partly because menarcheal age is a rather reliable and easily assessed measure of pubertal timing.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, no significant differences in BMC between men with early and late puberty were observed by late adolescence and early adulthood (17-28 years of age). (14) In a recently published longitudinal study (n ¼ 78 females, and n ¼ 85 males), Gilsanz and colleagues (13) found a strong reciprocal relation between DXA values of the whole body, spine, and upper and lower extremities, and variations in the timing of puberty within the normal range in both genders, concluding that late puberty influences peak bone mass negatively. However, the mean age at follow-up was 16.2 AE 0.9 years for boys, providing no information about the role of pubertal timing on adult BMD.…”
Section: Pubertal Timing and Bmd In Adolescentsmentioning
confidence: 99%
See 1 more Smart Citation